2010
DOI: 10.1089/ars.2010.3273
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the Cysteine Sensors in Kelch-Like ECH-Associated Protein 1

Abstract: The protein Kelch-like ECH-associated protein 1 (Keap1) is a cysteine-rich regulatory and scaffold protein. Human Keap1 contains 27 cysteines. Some of these cysteines are believed to mediate derepression of the transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2), which subsequently upregulates phase 2 enzymes, in response to electrophilic=oxidative assault. Some current models depict a highly select group of two and possibly a few more cysteine residues as key sensors. The assumptions and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 66 publications
3
69
0
1
Order By: Relevance
“…A widely accepted model for Nrf2 nuclear accumulation describes that a modification of the Keap1 cysteines leads directly to the dissociation of the Keap1-Nrf2 complex (33). Recently, one study suggested that Keap1 can be S-sulfhydrated at Cys151, which stimulates the dissociation of Nrf2 to enable its translocation to the nucleus (34).…”
Section: Discussionmentioning
confidence: 99%
“…A widely accepted model for Nrf2 nuclear accumulation describes that a modification of the Keap1 cysteines leads directly to the dissociation of the Keap1-Nrf2 complex (33). Recently, one study suggested that Keap1 can be S-sulfhydrated at Cys151, which stimulates the dissociation of Nrf2 to enable its translocation to the nucleus (34).…”
Section: Discussionmentioning
confidence: 99%
“…The best known is the Cullin 3 (Cul3) RING-box 1 (RBX1) E3 ubiquitin ligase complex, which needs the substrate adaptor protein Kelch-like ECHassociated protein 1 (Keap1) to ubiquitinate Nrf2 (Cullinan et al, 2004;Kobayashi et al, 2004;Zhang et al, 2004). Keap1 is a cysteine-rich regulatory protein located in the cytoplasm (Itoh et al, 1999;Holland and Fishbein, 2010). Keap1 dimerizes and binds Cul3 through its BTB domain (Furukawa and Xiong, 2005), while its Kelch domain is able to interact with the Neh2 domain of Nrf2 (Itoh et al, 1999;McMahon et al, 2006).…”
Section: Nrf2 Structure and Regulationmentioning
confidence: 99%
“…Under stress conditions, certain Keap1 cysteine residues are chemically modified, which prevents Nrf2 ubiquitination and degradation, allowing its stabilization and the transcription of its target genes (Holland and Fishbein, 2010) (Figure 1B). It has also been described that some electrophilic lipids, such as the cyclopentenone prostaglandin, 15-deoxy-Δ 12,14 -prostaglandin J 2 (which serves as a model to study the effects of lipid peroxidation products derived by the reaction of reactive oxygen/ nitrogen species with unsaturated fatty acids), are able to induce Nrf2 by modifying thiol groups of Keap1 (Levonen et al, 2004).…”
Section: Nrf2 Structure and Regulationmentioning
confidence: 99%
“…The cellular sensor protein Kelch-like ECH-associated protein 1 (Keap1) contains large numbers of sulfhydryl groups that can be modified by oxidants and electrophiles [10,11] . Under basal conditions, Keap1 associates with the key transcriptional factor nuclear factor erythroid 2-related factor 2 (Nrf2) and targets it for degradation [12] . When Keap1 is modified by either oxidative or electrophilic reagents, proteolysis is inhibited, and the dissociated Nrf2 translocates to the nucleus, binds to ARE, and promotes phase II enzyme gene expression [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Under basal conditions, Keap1 associates with the key transcriptional factor nuclear factor erythroid 2-related factor 2 (Nrf2) and targets it for degradation [12] . When Keap1 is modified by either oxidative or electrophilic reagents, proteolysis is inhibited, and the dissociated Nrf2 translocates to the nucleus, binds to ARE, and promotes phase II enzyme gene expression [12] . Therefore, oxidants and electrophiles might initiate the inducer signal by modifying Keap1 sulfhydryl groups, which can be further transduced by the Keap1-Nrf2 signaling pathway to activate cellular ARE.…”
Section: Introductionmentioning
confidence: 99%